Odpowiedź :
Odpowiedź:
pr BC
a = [tex]\frac{-1 - 1}{3 -(-1)}[/tex] = - 0,5
y = - 0,5 x + b A = ( 2, 4)
więc 4 = - 0,5* 2 + b
4 = -1 + b ⇒ b = 5
Odp. y = - 0,5 x + 5 - jest to prosta równoległa do pr BC
======================
II p
y =a x + b A =( 2, 4)
więc
4 = 2 a + b ⇒ b = 4 - 2 a
y = ax + 4 - 2 a
lub
a x - y + 4 - 2 a = 0
Ma być jednakowo oddalona od punktów B =( -1, 1) i C = ( 3, - 1)
zatem
[tex]\frac{I -1 a - 1 + 4 -2 a I}{\sqrt{a^2 + 1} }[/tex] = [tex]\frac{ I 3 a + 1 + 4 -2 a I}{\sqrt{a^2 + 1} }[/tex] / * [tex]\sqrt{a^2 + 1}[/tex]
I --3 a + 3 I = I a + 5 I
a + 5 = -3 a + 3 lub a + 5 = 3 a - 3
4 a = - 2 2 a = 8
a = - 0,5 a = 4
b = 4-2*(-0,5) = 5 b = 4 - 2*4 = - 4
y = -0,5 x + 5 lub y = 4 x - 4
=====================================
Szczegółowe wyjaśnienie: